Keabsahan Pemeriksaan Saksi secara Bersama-Sama di Persidangan sebagai Perwujudan Asas Cepat Sederhana dan Biaya Ringan - Ubaidillah, Lutfian (Indonesia Berdaya, 2024)
To implement criminal law, it is necessary to take steps to maintain the legal order of society. This method is known as criminal procedural law. The purpose of the Criminal Procedure Code is to seek and obtain or at least approach the material truth, the complete truth. The Indonesian criminal justice system consists of the police, prosecutors, district courts and correctional institutions as law enforcement officers. The four organs are closely related and limit each other. With the aim of being able to explain an alleged criminal act, evidence is needed to support that a crime has occurred. Evidence is directly or indirectly related to the crime. Direct evidence includes victims who suffered physically or mentally, including witnesses who saw or heard that a crime had occurred. Examination of witnesses has an important role in criminal proceedings by following the principles of unnus tetis nulus tetis (witnesses are not witnesses) and testimonium de auditu (statements of other people are not valid evidence). In the process of examining witnesses, many things go together. This is possible because of the principle of justice which is fast, easy and cheap. Because based on this principle, both the public prosecutor and the judge are obliged to review the defendant's case as soon as possible, especially for defendants who are in detention. That if the witness examination is carried out simultaneously. This can be done because of the principle of a fast, simple and low-cost trial, but how can the validity of witnesses who are examined jointly at trial be known, the implementation of witness examinations between mitigating and aggravating ones is not directly examined together, but separately and what distinguishes it is the time when the examination is carried out because it involves the validity and provision of interrelated information. In this study the authors used a normative method using a statutory approach and the legal materials used were primary legal materials, namely laws and regulations related to the issues to be discussed and secondary legal materials obtained from all publications on law including books and, law dictionaries.